Electrical machines, drives, and power systems - Wildi, Theodore (Prentice Hall, 1997)
A theoretical, practical, multidisciplinary introduction to modern electric power. This edition has been expanded to reflect the rapid changes that have occurred in power technology, and adds industry application problems to the standard end-of-chapter exercises.